VCP/p97 modulates PtdIns3P production and autophagy initiation - Wrobel, Lidia (Autophagy, 2021)
VCP/p97 is an essential multifunctional protein implicated in a plethora of intracellular quality control systems, and abnormal function of VCP is the underlying cause of several neurodegenerative disorders. We reported that VCP regulates the levels of the macroautophagy/autophagy-inducing lipid phosphatidylinositol-3-phosphate (PtdIns3P) by modulating the activity of the BECN1 (beclin 1)-containing phosphatidylinositol 3-kinase (PtdIns3K) complex. VCP stimulates the deubiquitinase activity of ATXN3 (ataxin 3) to stabilize BECN1 protein levels and also interacts with and promotes the assembly and kinase activity of the PtdIns3K complex. Acute inhibition of VCP activity impairs autophagy induction, demonstrated by a diminished PtdIns3P production and decreased recruitment of early autophagy markers WIPI2 and ATG16L1. Thus, VCP promotes autophagosome biogenesis, in addition to its previously described role in autophagosome maturation.